Considerations on unfair terms in bank credit contracts - Chirieac, Roxana (Technium Social Sciences Journal, 2020)
Over the last few years, we have seen an increasingly number of case law that was presented before national courts as well as the European Court of Justice concerning unfair terms in bank credit contracts. This subject was raised especially during the crisis in which the swiss francs had appreciated, leading numerous customers that had previously taken bank loans in this currency unable to pay back loans that had risen in almost half their value. Development in international and national legislation, such as Law no. 193/2000 concerning unfair terms in contracts concluded between professionals and consumers, that transposed into our national legislation the Council Directive 93/13/EEC of 5 April 1993 on unfair terms in consumer contracts, both restricted or banned the use of such practices and were in force long before the crisis was generated. This however did not stop credit institutions from inserting these types of clauses in the contracts that they had concluded. The issue that we aim to treat in this article is whether the recent practices of credit and bank institutions has changed over the course of the last few years, given the development of jurisprudence that most often than not condemns abusive or unfair terms in credit agreements with consumers.